Anti‐herpetic drugs: A potential way to prevent Alzheimer's disease?. (31st December 2021) - Linard, Morgane; Bezin, Julien; Hucteau, Emilie; Joly, Pierre; Letenneur, Luc; Garrigue, Isabelle; Dartigues, Jean‐François; Pariente, Antoine; Helmer, Catherine
Abstract: Background: Considering the potential implication of Herpes viruses in the development of dementia, anti‐herpetic drugs (AHD) may represent a new means of prevention. Method: Using a medico‐administrative database, we assessed the association between the intake of systemic AHD and the incidence of i) dementia, ii) Alzheimer's disease (AD) and iii) vascular dementia (VaD) among 68 291 participants over 65 followed between 2009 and 2017. Cox models using systemic AHD as time‐dependent variable were adjusted for age, sex, being beneficiary of a complementary health insurance scheme for low‐income people, the presence of several co‐morbidities (hypertension, diabetes, hypercholesterolemia, stroke, heart diseases), the intake of anti‐inflammatory drugs, the number of consultations, and the number of different medications the year before inclusion. Result: 9.7% of the participants (n=6642) had at least one intake of systemic AHD and 8883 incident dementia were identified. The intake of at least one systemic AHD was significantly associated to a decreased risk of AD (aHR 0.85 95% confidence interval [0.75‐0.96], p=0.009) and, to a lesser extent regarding p‐values, to both dementia any cause (aHR 0.90 [0.82‐0.99], p=0.03) and VaD (aHR 0.80 [0.65‐0.995], p=0.045). As the percentage of participants with a regular intake was very low (among those with at least one intake of systemic AHD, the median number of deliveries per year of follow‐up was 0.12), the efficacy of regular intake of AHD could not be evaluated. Conclusion: Taking at least one systemic AHD during follow‐up was significantly associated to a risk reduced by 15% of developing AD. Despite the low percentage of participants with a regular intake during the follow‐up, this association may reflect a protective impact of systemic AHD on the prevention of dementia in particular considering the possibility of more regular treatment in the period preceding the inclusion. It also highlights the limitations of medico‐administrative databases to assess the efficacy of a regular intake of systemic AHD given their current use in clinical practice. Thus, given the growing body of evidence supporting the infectious hypothesis, preventive clinical trials with prolonged treatment by systemic AHD are urgently needed.